What can we learn today from the dialogue between Jesuits and Chinese «Literati»? - Vermander, Benoît (Razón y fe, 2019)
The encounter between Jesuits and Chinese literati was decisive for the cultural evolution of China and Europe. What happened at that time can be valuable for contemporary cultural and spiritual encounters. Therefore, the archaeology of sinology helps us to explore reflectively how our current research efforts fit into the dialogical construction of a global community. In the history of Sinology, the dialogue between Jesuits and Chinese literati is a major historical milestone and the dialogical effort established during this first formative period of Sinology can inspire new dialogues in various communities. Dialogue appears within, but also, and most importantly, defines a community environment; it allows for connecting different environments in a new space of conversation through the continual transformation of their linguistic rules.
Keywords: Matteo Ricci; sinology; comparative theology; intercultural dialogue; China